المختصرات التفسيرية بين أصالة الاستمداد ومتطلبات الواقع المعاصر - بوخزنة, حمزة (University of Eloued جامعة الوادي, 2024)
ملخص: هذا المقال بعنوان: المختصرات التفسيرية بين أصالة الاستمداد ومتطلبات الواقع المعاصر" المختصر في تفسير القرآن الكريم أنموذجا " . يعالج إشكالية تتعلق ببيان أهمية هذا النوع من التفاسير الوجيزة من خلال الكشف عن الآليات المتبعة فيها حديثا بغية تقديم تفسير للقرآن يجد فيه القارئ كل ما يتعلق بمختلف شؤون وواقع حياته الروحية والمادية دون تطويل ولا حشو للروايات وغيرها. وقد قسمنا الدراسة إلى ثلاثة محاور أساسية؛ جاء المحور الأول للتعريف بمدونة "المختصر في تفسير القرآن الكريم" وطريقة تأليفه. والثاني لبيان طرق وأصول الاستمداد التفسيري فيه. والثالث لعرض المسالك التجديدية في هذا التفسير التي تراعي طبيعة الواقع المعاش. ومن أبرز النتائج المتوصل إليها أن أصحاب هذا التفسير كانوا على وعي كبير بأهمية أصول التفسير وقواعده إضافة إلى إدراكهم التام بمتطلبات المعاصرة من عرض مقاصد السور وأغراضها والتركيز على الجوانب الإصلاحية والتربوية والأخلاقية... فيها. This article is entitled: Abbreviations interpretations of the Holy Quran between the origins of interpretation and requirements of contemporary reality “The Abbreviation in the Interpretation of the Holy Qur’an as a Model” . It studies a problem related to the importance of this type of interpretation by revealing the mechanisms used in it recently in order to provide an easy interpretation of the Qur’an in which the reader finds everything related to the various affairs of his spiritual and material life. We have divided the study into three main axes; The first axis came to define this interpretation and the way it was composed. The second is to explain the origins of the interpretation adopted in it. The third is to present the contemporary regenerative paths in this interpretation. Among the most prominent results reached is that the authors of this interpretation were very aware of the importance of the principles of interpretation and its rules in explaining the meanings, in addition to their full awareness of the requirements of contemporary times through their focus on the purposes of The Surahs and their purposes by revealing the reformist, educational and ethical aspects... in them.
المختصر في تفسير القرآن الكريم أنموذجا
Keywords: المختصرات; التفسير; Abbreviations; interpretation; the Holy Quran; the origins of interpretation; contemporary